PROFIL ASAM AMINO EKSTRAK CACING TANAH (LUMBRICUS RUBELLUS) TERENKAPSULASI DENGAN METODE SPRAY DRYING - Hayati, Septi Nur; Herdian, Hendra; Damayanti, Ema; Istiqomah, Lusty; Julendra, Hardi (Teknologi Indonesia, 2011)
Antibiotics in poultry were widely used as growth promotor and anti-infective. When antibiotics were used continuously for long periods, it caused microbial resistance. Various attempts were made to replace antibiotics along with the increasing of trend towards demand for healthy, safe and free from harmful residues of livestock products. One of them was application of earthworm which contains high protein and complete amino acids. Earthworms were extracted into water extract form by decoct method. Water extract form had some weaknesses. It was necessary to formulate into a solid dosage form which was more stable, reproducible, and practical. The selected formulation was encapsulation by spray drying method. Quality control of feed additives can be seen from biological value. Biological value correlated positively with amino acids equilibrium or Essential Amino Acid Index (EAAI). The result showed that earthworm extract had both essential and non-essential amino acids higher than earthworm meal and encapsulated earthworm extract. The highest essential amino acid in earthworm meal was isoleucine (3.14%), in earthworm extract was lysine (8.16%), and in encapsulated earthworm extract was leucine (1.71%). The highest non-essential amino acids in earthworm meal and encapsulation of earthworm extract were glutamic acid, respectively 7.67% and 1.87%, while the earthworm extracts was serine (14.52%). The high value of IAAE in earthworm extract showed that the extraction method resulted better amino acid balance (69.87%) than earthworm meal (58.67%). While the value IAAE of encapsulated earthworm extract showed that levels of essential amino acid balance was lower (16.05%) than the earthworm meal (69.87%) and the earthworm extract (58.67%).